Assosiation of COVID-19 Infection and Acute Mesenteric Ischemia - Kostovski, Ognen; Lazarova, Irena; Popchanovski, Bojan; Kostovska, Irena (The First Faculty of Medicine of Charles University - Karolinum press, 2023)
COVID-19 is an infectious disease that is considered to be a thrombo-inflammatory disorder. The study was aimed to determine the prevalence of COVID-19 in patients with acute mesenteric ischemia (AMI) and the outcomes of surgical treatment in relation to COVID-19. A total of 140 patients were included in this multicentric study divided into two groups: the test group (n=65) consisted of cases of AMI detected during the COVID-19 pandemic and the control group (n=65) consisted of cases of AMI detected before the pandemic. Test group patients were classified as COVID-positive (COVID+), or COVID-negative (COVID–) if they tested positive, respectively negative test for COVID-19 on admission. Primary outcomes were: prevalence of COVID-19 infection among test group patients, association between COVID-19 infection and inoperability, and between COVID-19 and treatment outcome. Secondary outcomes were association between each blood parameter and inoperability and treatment outcome. There were no statistically significant differences between inoperability and COVID-19 positivity on admission, overall mortality between the control group and the test group and overall mortality between COVID+ and COVID– patients, as well as among those patients that have been surgically treated (p>0.05). There were statistically significant differences between serum amylase levels (p=0.034), and serum LDH levels (p=0.0382) and inoperability, between serum LDH levels and postoperative mortality (p=0.0151), and overall mortality (p=0.00163). High level of LDH and serum pancreatic amylase are associated with a higher rate of inoperability and a higher postoperative and overall mortality rate. COVID-19 does not seem to independently influence the treatment outcome of AMI.
Keywords: Acute mesenteric ischemia; COVID-19; SARS-nCoV2; prevalence; outcome